Pertimbangan Hakim Dalam Penetapan Wali Adhal Akibat Kepercayaan Di Pengadilan Agama Jombang - Naomi, Clara Sophia; Zuhda Mila Fitrianna (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This Study Discusses The Legal Considerations Of Judges In Appointing A Guardian Due To The Refusal Of A Blood Guardian Influenced By Kejawen Beliefs. Kejawen, As One Of The Local Beliefs Of The Javanese People, Has Its Own Value System Which In Some Cases Conflicts With The Principles Of Islamic Law, Particularly In The Context Of Marriage. This Study Was Motivated By A Real Case In The Jombang Religious Court, Where A Biological Father Refused To Be His Child's Marriage Guardian Due To Pressure From Relatives Who Adhered To Kejawen Teachings, Even Though The Marriage Fulfilled The Requirements Under Islamic Law. The Study Used A Juridical-Empirical Approach, With Data Obtained Through Court Observation, Document Study, And Analysis Of Relevant Legal Norms. The Results Of The Study Show That The Judge's Considerations Were Based On The Principles Of Maqashid Syariah, The Protection Of Women's Rights, And The Principle Of Substantive Justice. The Judge Appointed A Guardian Judge As A Legal Solution Because The Guardian's Refusal Was Deemed Invalid According To Islamic Law. These Findings Demonstrate The Importance Of Harmonizing Religious Law, State Law, And Local Culture In The Practice Of Religious Courts.